Triple talaq: revocable or irrevocable? an analysis in the light of Maqasid approach - Subhani, Zulqernain Haider; Ghalia, Bouhedda; Ali, Mohammed Farid (Department of Syariah Judiciary Malaysia & Ahmad Ibrahim Kulliyyah of Laws, IIUM, 2021)
Triple Talaq which is also referred to as instant Talaq has been a point of dispute and discussion among Muslim scholars and jurists since the very early period of Islam regarding whether this will be considered one revocable Talaq, or it will be regarded as three and irreversible one. Ironically, both the opponents and the proponents refer to the almost same verses and Prophet’s traditions to justify their positions with little exclusive grounds. It has become more critical today as it has caused conflicts between civil courts of several countries and Shari’ah boards as was the case recently in India. This paper tries to relook into the issue from Maqasid al-Shari’ah perspective as scholars say that when there are shreds of evidence on both sides, then Maqasid plays an essential role in giving preference of one position over the other as well as reconciliation between opposing opinions with different contexts. To achieve the goal, textual and comparative analysis methods are used in addition to three levels of Maqasid as a tool of analysis to decipher the general, specific and particular objectives of the Shari’ah, as well as to study the evils (Mafsada) and interests (Maslaha) of the issue. The study finds that Maqasid-imbued-preference is an effective tool to reconcile conflicting issues and Malaysia stands as a good example of regulating and institutionalizing the procedure of talaq according to the Maqasid which essentially solves the problem of triple talaq.